The Influence of The Amaunt of Members’s Saving, The Amount of the Loan to the Cooperative Profit (SHU) with Interest Rates as a Moderating Variable (Study in the KPRI-GHB DPU, District of Sukoharjo) - Suranto, Suranto (STIE AUB Surakarta)
This research aims are to test empirically and analyze the influence of the amaunt of members’s saving, the amount of the loan to the cooperative profit (SHU) with interest rates as a moderating variable in the KPRI-GHB DPU district Sukoharjo. This research is quantitative research to test the hypothesis. The data used in this research is financial statement KPRI-GHB DPU district. Sukoharjo period of 2010-2014. The data obtained are tested using regression test, t-test, F test, R ² test. Results of this research prove that the amount of savings is a significant negative effect on cooperative’s profit (SHU), interest rates is significantly and negatively able to moderate correlation to the amount of savings on cooperative’s profit (SHU), loan amount and there is a significant positive effect on cooperative’s profit (SHU), interest rates is not significantly and positive able to moderate the relationship with the loan amount on cooperative’s profit (SHU). The results also proved that 50.8% cooperative’s profit (SHU) can be explained by the amount of deposits, loan amount, interest rate and the remaining 49.2% is explained by other variables outside of the variables used.Keywords: the amount of saving, loan amount, interest rate, and cooperative’s profit